2018
DOI: 10.1016/j.psyneuen.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded protein response and associated alterations in toll-like receptor expression and interaction in the hippocampus of restraint rats

Abstract: Recent evidence suggests that the cellular response to stress often elicits the unfolded protein response (UPR), which has an active role in major depression in emotionally relevant regions of the brain, such as the hippocampus. Much of the UPR activity has been found to be coalesced with the pro-inflammatory environment of the depressed brain. Specifically, downstream transcriptions of pro-inflammatory cytokines and increased regulation of candidate inflammatory mediators, such as toll-like receptors (TLRs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…IL-6 and TNF-α are also involved in the induction of indoleamine 2,3-dioxygenase, which depletes tryptophan and induces depression 71 , 72 . Recently, we reported that the pharmacological manipulation of cellular stress pathways can induce depression phenotype in rats, which involved TNF-α, NF-κB, and TLRs 73 . Our findings of GR signaling along with immune response mediated through differentially regulated synaptic genes suggest that they may, either independently or in concert, be playing a critical role in compromised immune functions and may be responsible for the development of depressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 and TNF-α are also involved in the induction of indoleamine 2,3-dioxygenase, which depletes tryptophan and induces depression 71 , 72 . Recently, we reported that the pharmacological manipulation of cellular stress pathways can induce depression phenotype in rats, which involved TNF-α, NF-κB, and TLRs 73 . Our findings of GR signaling along with immune response mediated through differentially regulated synaptic genes suggest that they may, either independently or in concert, be playing a critical role in compromised immune functions and may be responsible for the development of depressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…All samples had 260/280 ratio >1.8 and demonstrated 28S:18S rRNA ratio of 2:1 on agarose gel. The single-stranded cDNA was prepared following the previously described method (Timberlake et al, 2018). Following the preparation of mRNA specific first strand cDNA, relative transcript abundance of coding genes was measured with quantitative real-time PCR (Stratagene MxPro3005, La Jolla, CA, United States) method.…”
Section: Rna Isolation and Qpcr-based Gene Expressionmentioning
confidence: 99%
“…The single-stranded cDNA was prepared as described previously [28]. Following the preparation of mRNA specific first strand cDNA, 1 μg total RNA was reverse transcribed using M-MLV Reverse Transcriptase (Invitrogen, NY, USA) and oligo (dT) primer.…”
Section: Rna Isolation and Qpcr-based Gene Expression Analysis In Ratmentioning
confidence: 99%